2012
DOI: 10.18553/jmcp.2012.18.s1-b.1
|View full text |Cite
|
Sign up to set email alerts
|

Summary of AHRQ’s Comparative Effectiveness Review of Disease-Modifying Antirheumatic Drugs for Children with Juvenile Idiopathic Arthritis

Abstract: JIA is a chronic inflammatory disease affecting approximately 300,000 children and adolescents in the United States.1 Initially manifesting with inflammation, swelling, pain, and stiffness of the joints, the disease as no apparent or known cause. JIA is a clinical diagnosis based on several actors including the number of affected joints and the involvement of other tissues (e.g., the skin and lymphoid tissues), and JIA has 7 categories: systemic-onset arthritis, oligoarthritis, rheumatoid-factor positive polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…Thus, the prescribing doctor is in a legal gray area, especially because there is only very limited safety data for long‐term treatment of psoriasis in this age group . With respect to children and adolescents, experience with conventional systemic therapeutic agents also used in the treatment of psoriasis comes from other approved indications such as juvenile arthritis and Crohn's disease, as well as following organ transplants . Thus, according to a German consensus recommendation, children and adolescents with psoriasis requiring systemic therapy should initially be treated with methotrexate and cyclosporine, or alternatively fumaric acid esters (FAEs) and retinoids .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the prescribing doctor is in a legal gray area, especially because there is only very limited safety data for long‐term treatment of psoriasis in this age group . With respect to children and adolescents, experience with conventional systemic therapeutic agents also used in the treatment of psoriasis comes from other approved indications such as juvenile arthritis and Crohn's disease, as well as following organ transplants . Thus, according to a German consensus recommendation, children and adolescents with psoriasis requiring systemic therapy should initially be treated with methotrexate and cyclosporine, or alternatively fumaric acid esters (FAEs) and retinoids .…”
Section: Introductionmentioning
confidence: 99%
“…Methotrexate has been a mainstay of therapy with adequate effi cacy for many children [ 19 ]. It has been the most commonly used secondline agent for children with JIA of all subtypes for many years but has been less effective in SoJIA than in other subtypes.…”
Section: Other Agentsmentioning
confidence: 99%
“…The patient populations in randomized clinical trials are often much more homogeneous than standard clinical populations and these trials seldomly compare active treatments with each other (especially in patients with JIA) because of the numbers of patients needed to do so. A 2012 formal literature review 46 focused on the comparative effectiveness of biologic agents and traditional DMARDs; the authors concluded that the publications on JIA studies are robust and reliable enough to show that the biologic agents tested in randomized trials decreased the rate of flares, and that methotrexate was superior to other conventional non biologic therapies. 46 However, the published literature was insufficient to address the effects of the treatments on radiologic progression or health status, the comparative rates and types of adverse events, and the precise determination of the risk:benefit ratio for each therapy.…”
Section: Treating To Remissionmentioning
confidence: 99%
“…A 2012 formal literature review 46 focused on the comparative effectiveness of biologic agents and traditional DMARDs; the authors concluded that the publications on JIA studies are robust and reliable enough to show that the biologic agents tested in randomized trials decreased the rate of flares, and that methotrexate was superior to other conventional non biologic therapies. 46 However, the published literature was insufficient to address the effects of the treatments on radiologic progression or health status, the comparative rates and types of adverse events, and the precise determination of the risk:benefit ratio for each therapy. 46 This formal review of the literature was demanding but highlights areas to address in future studies.…”
Section: Treating To Remissionmentioning
confidence: 99%
See 1 more Smart Citation